The Influence Of Dual Role Confectionary And Work Environment On Employee Performance - Vina Sahnia Fitri; Eti Arini (BIMA Journal (Business, Management, & Accounting Journal), 2021)
HR is perhaps the most decisive asset for organizational prosperity. In today's era of globalization being enforced by today's rapidly increasing knowledge and innovation, advice is progressively blurring the limitations of the types of work for people. The title of thiis researrch is The Effect of Multiple Role Conflict and Worrk Enviironment on Emplloyee Perforrmance (Case Study of Employee Indomaret, Bengkulu City). Thiis type of researrch is a quantitative descriptive research type, the object of this research is per Indomaret area in the city of Bengkulu, namely the Hybrid area, Panorama, West Circle, KM 6.5, Derivation, Padang teak, Tanah Broken, Suprapto, Rawa makmur and Kampung Bali. With the metthod of collectiing datta by means of observation, distributing questionnaires or questionnaires. The number of respondents in thiis sttudy were 50 people. By using data analysis techniques using Multiiple Liinear Regressiion Analysiis Test, and Hypothesis Test, namely test t and test f.The resullts of thiis sttudy can be concluded that the multiple role conflict variable has a negative and signifiicant effeect on employee performance, meaning that employee performance can increase if the dual role conflict can be suppressed or reduced, while the worrk enviironment variiable has a posiitive and signifiicant efefect on employee performance, meaning that employee performance can increase. if the workplace has a safe and comfortable environment and is supported by good air circulation.